2017
DOI: 10.1021/acs.jafc.6b05104
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Caprine Milk Oligosaccharides at Different Lactation Stages Analyzed by High Performance Liquid Chromatography Coupled to Mass Spectrometry

Abstract: Changes of the abundance of caprine milk oligosaccharides (CMO) at different lactation stages have been evaluated by hydrophilic interaction liquid chromatography coupled to mass spectrometry (HILIC–Q MS) and nanoflow liquid chromatography–quadrupole-time-of-flight mass spectrometry (nano-LC-Chip–QTOF MS). Eight major oligosaccharides (OS) were quantified at different lactation stages by HILIC–Q MS, while the use of nano-LC-Chip–QToF MS allowed expanding the study to forty-nine different OS by monitoring neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
3
28
2
Order By: Relevance
“… 25 30 The oligosaccharide composition of goat milk (gMOS) has been studied 24 , 27 29 , 31 35 and compared to other domesticated animals. 24 , 29 A few studies have reported variations of oligosaccharides at the goat breed level, 25 , 26 over time during lactation, 25 , 28 , 36 in parity, 26 or at the individual goat level. 37 Such information is considered interesting, because gMOS are more abundant than bMOS and contain certain structures that are in common with hMOS ( Schemes 1 and 2 ).…”
Section: Introductionmentioning
confidence: 99%
“… 25 30 The oligosaccharide composition of goat milk (gMOS) has been studied 24 , 27 29 , 31 35 and compared to other domesticated animals. 24 , 29 A few studies have reported variations of oligosaccharides at the goat breed level, 25 , 26 over time during lactation, 25 , 28 , 36 in parity, 26 or at the individual goat level. 37 Such information is considered interesting, because gMOS are more abundant than bMOS and contain certain structures that are in common with hMOS ( Schemes 1 and 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The major glycosylated components in human milk include oligosaccharides (HMOs), glycoproteins, and glycolipids (12). Recent advances in mass spectrometry (MS)-based tools have provided a view of the HMOs’ structures that could be decorated with either fucose and/or sialic acid moieties (13, 14). The fucosylated HMOs were found to function as prebiotics for infant-favorable Bifidobacterium strains and vary significantly between mothers of different secretory statuses, which is determined by single nucleotide polymorphisms (SNPs) of the maternal fucosyltransferase 2 ( Fut2 ) gene (15).…”
Section: Introductionmentioning
confidence: 99%
“…The fat content was determined by ether extraction (AOAC 2000). Lactose content was quantified by ion chromatography (ICS‐3000, Dionex Limited., California) as described by Martin‐Ortiz et al () in order to remove residual protein and fat. Mineral was measured according to Jørgensen et al () using coupled plasma mass spectrophotometer (7700X, Agilent Technologies Inc., California).…”
Section: Methodsmentioning
confidence: 99%